مخبربحوث ودراسات في الميديا الجديدة.. تجربة رائدة... نظرة استشرافية نحو التحول للتكوين بالممارسة - روبورتاج مصور- - زروقي مريم; لرقط حسين (-جامعة محمد بوضياف -المسيلة, 2024)
ملخص الدراسة: من خلال هذا الروبورتاج المصور حاولنا أن نلمس أهمية تقديم تكوين جيد ومميز للطالب الجامعي داخل هياكل فرعية تابعة للجامعة كمراكز البحث العلمي، وارتأينا هنا لعرض تجربة مخبر بحوث ودراسات في الميديا الجديدة بكلية العلوم الإنسانية والاجتماعية بجامعة المسيلة والذي قدم نشاطات إعلامية عديدة في فترة تعتبر قصيرة مليئة بتكوين مكثف للطلبة من قسم الإعلام في مجال صناعة وإنتاج محتويات إعلامية كلها بإبداع طلابي بحت، ونشرها على الانترنيت وإبراز قدرات ومواهب الطلبة التي تساعدهم في بناء شخصية مهنية قوية عند التوجه نحو سوق العمل بعد التخرج. Abstract: Through this report, we tried to touch on the importance of providing good and distinctive training for university students within subsidiary structures of the university such as scientific research centers. We chose here to showcase the experience of the Laboratory of Research and Studies in New Media at the Faculty of Humanities and Social Sciences at the University of M’sila, which presented numerous media activities in a short period filled with intensive training for students from the Department of Media in the field of manufacturing and producing media content, all with pure student creativity, and publishing them on the internet and highlighting the capabilities and talents of the students that help them in building a strong professional personality when heading towards the labor market after graduation.